Performance of Reinforced Concrete Shear Wall In Dual Structural System: A Review - Suwal, Rajan; Khawas, Aakarsha (Nepal Journal of Science and Technology, 2022)
A dual structural system consists of a momentresisting frame, and vertical reinforced concrete walls called shear walls. Shear walls used in tall buildings are generally located around elevator cores and stairwells. Many possibilities exist in a tall building regarding the location, shape, number, and arrangement of shear walls. Shear walls generally start at the foundation level and are continuous throughout the building height. Their thickness can be as low as 150mm in lowrise to medium-rise buildings or as high as 400mm in high-rise buildings. To establish an effective lateral force-resisting system, the shear walls are located in preferable positions in a structure that minimizes lateral displacements. The shear walls are situated in ideal locations to be symmetrical and torsional effects get reduced. Based on the comparison of various literature regarding the shear wall positions, the shear wall placement at the core or the corners of the structure symmetrically gives the best performance to reduce displacement and story drift. Also, lateral displacement diminishes when the shear wall’s thickness increases.